2011
DOI: 10.1029/2010jb008032
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and geometric controls on the structural evolution of pit crater and caldera subsidence

Abstract: [1] Pit craters and calderas are volcanic depressions produced by subsidence of a magma reservoir roof. To identify how geometric and mechanical factors may influence the structural evolution of this subsidence, we used two-dimensional distinct element method numerical models. The reservoir host rock was represented as an assemblage of bonded circular particles that interact according to elastic-frictional laws. Varying particle and bond properties produced a range of bulk material properties characteristic of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
108
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 84 publications
(123 citation statements)
references
References 66 publications
(168 reference statements)
15
108
0
Order By: Relevance
“…Also, contrary to FEM, it is not possible to specify a priori the stress-strain response of the assemblage. Therefore it is necessary to carry out calibration of particle properties to the emergent rock physical properties (Egholm et al, 2007;Holohan et al, 2011). Discrete element simulations of thrust-related structures have been carried out by Finch et al (2003), Strayer and Erickson (2004), Cardozo et al (2005), , Benesh et al (2007), ), Zhang et al (2013 and Gray et al (2014).…”
Section: Mechanical Modelsmentioning
confidence: 99%
See 3 more Smart Citations
“…Also, contrary to FEM, it is not possible to specify a priori the stress-strain response of the assemblage. Therefore it is necessary to carry out calibration of particle properties to the emergent rock physical properties (Egholm et al, 2007;Holohan et al, 2011). Discrete element simulations of thrust-related structures have been carried out by Finch et al (2003), Strayer and Erickson (2004), Cardozo et al (2005), , Benesh et al (2007), ), Zhang et al (2013 and Gray et al (2014).…”
Section: Mechanical Modelsmentioning
confidence: 99%
“…In 2D, we have the possibility to implement collapse and biaxial compression simulations. Such tests are performed on a subportion of the system in order to evaluate multiple sets of values of particle properties within acceptable runtimes (Finch et al, 2004;Holohan et al, 2011;paper 1). Collapse simulations allow the measure of the static angle of repose of the material, and biaxial tests at 24 several confining pressures allow the measure of the failure envelope of the material.…”
Section: Demmentioning
confidence: 99%
See 2 more Smart Citations
“…DEM has been used in the past to investigate collapse phenomena (e.g., Bym et al, 2013;Holohan et al, 2011Holohan et al, , 2015. Bym et al (2013) show that DEM reproduces very well empirically observed subsidence profiles, while Holohan et al (2011Holohan et al ( , 2015 show the evolution of fractures and stress during the collapse of a volcanic caldera because of the withdrawal of a magmatic body.…”
Section: Methodsmentioning
confidence: 96%